Implications Of Environmental Factors On The Productivity Of Selected Small And Medium Scale Enterprises In Rivers-State - Tambari, Jonah Charles; Chioma, Aginah; Ononogbo, Martins C (Archives of Business Research, 2018)
this study is on implications of environmental factors on the productivity of small and medium scale enterprises in River-state: a study of selected SMES in Portharcourt. The study took a descriptive survey approach and relied on a five point likert scale questionnaire as its major source of data. The study covered a population of 150 members of staff of three SMEs selected from the three senatorial zones of Rivers-state from where a sample of 124 respondents was drawn using purposive sampling technique. The data gathered was analyzed using multiple regressions with the aid of 20.0 version of the statistical package for social sciences (SPSS 20.0). Results obtained from the joint test shows that environmental factors affects the productivity of SMEs. However, the results of the individual test suggest that the implications of economic and political environmental factors are severely felt by SMEs than the socio-cultural factors. Based on the results obtained, the paper drew three conclusions and advanced three recommendations among which were; that SMEs should strategically engage in constant monitoring and conducting of environmental scanning, SMEs should learn to align their operational strategies with present market and environmental realities. This calls for a regular update and adjustment in strategies and that Government should provide an urgent safety net for SMEs against undue taxation and other harsh economic policies that tend to hamper their productivity